Gambaran Kualitas Hidup - Fungsi Penglihatan Pasien dengan Glaukoma di Poli Mata Rumah Sakit di Kabupaten Jember - Siswoyo Siswoyo; Kushariyadi Kushariyadi; Deby Febriyani Purwitasari (Pustaka Kesehatan, 2019)
Glaucoma is a neuro-optic disease characterized by an increase of IOP and progressive and incurable. Most cases of glaucoma do not show initial symptoms until there is a decrease in vision to blindness. This visual impairment can have an impact on the individual's ability to doing daily activities and will affect the quality of life-related to the visual function. This study aims to analyze the quality of life (vision function) in glaucoma patients at dr. Soebandi hospital, Baladhika Husada hospital, and Bina Sehat hospital in Jember Regency. The type of research is descriptive quantitative. 73 respondents were obtained by purposive sampling technique. Data collection using the Glaucoma Quality of Life 15 questionnaire. Data analysis using univariate. The results of the study were 47 respondents (64.4%) had a good quality of life and 26 respondents (35.6%) had a poor quality of life. In conclusion, the quality of life (vision function) of glaucoma patients is in a good category. This means that respondents can still do their daily activities independently with the help of glasses or not. The implication of this research is that nurses act as educators and counselors to provide all information about glaucoma and determine further planning to help improve patients' quality of life.